UPAYA GREENPEACE DALAM MENANGANI KERUSAKAN HUTAN TROPIS AMAZON AKIBAT DEFORESTASI DI BRASIL - ., Mariamlie; Takwa, Tuah Kalti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research discusses how Greenpeace's efforts to deal with the damage to the Amazon tropical forest due to Brazilian deforestation during the leadership of Jair Messias Bolsonaro during the 2019-2022 period. The average concentration of deforestation during the reign of Jair Bolsonaro increased sharply, this is in line with the report of the Global Crime Index organization in 2022, if deforestation of the Brazilian Amazon tropical forest becomes an important highlight and shapes global dynamics. Greenpeace as an environmental INGO (International Non Governmental Organization) has made a series of efforts to minimize deforestation and its impacts, especially for indigenous peoples. The researcher used a qualitative descriptive research method with a literature study approach. Data and information were collected and analyzed to understand the phenomenon studied. The results showed that Greenpeace Brasil has not succeeded in influencing the Brazilian government's policy towards deforestation control through a series of campaigns and advocacy. Greenpeace Brasil's position as a non-governmental organization has limitations as an initiator, facilitator, mediator and reconciler actor. Therefore, Greenpeace cannot directly change every anti-environmental regulation of the Bolsonaro government. By presenting scientific evidence through various reports, the organization has succeeded in shaping public opinion in favor of deforestation control measures and providing valuable input for policy change. Greenpeace. Greenpeace Brazil strives for a better life through the socialization of preventive and repressive actions for indigenous communities around the Amazon Forest region of Brazil. Keywords: Deforestation, Greenpeace, Amazon Tropical Forest, Efforts